Localized Bilateral Superior and Inferior Orbital Neurofibroma in the Absence of Neurofibromatosis - Rojas-Correa, Daniela; Bengoa-González, Álvaro; Mencía-Gutiérrez, Enrique; Hernández-Laín, Aurelio; Salvador, Elena; Martín-Clavijo, Agustín; Jiménez-Almonacid, Justino; Lago-Llinás, María-Dolores (Case reports in ophthalmological medicine, 2021)
Localized or isolated neurofibromas are peripheral nerve sheath tumors. They are rare in the orbit and occur without a systemic neurofibromatosis. There are few cases of bilateral tumors reported but none affecting both supraorbital and infraorbital nerves. We report a 45-year-old female who presented an extraconal mass in the right orbit as an incidental finding in a head computer tomography, without ocular symptoms. Magnetic resonance image showed a well-defined oval mass in the right supraorbital and infraorbital nerves, of similar characteristics, as well as smaller masses in the left supraorbital and infraorbital nerves. A progressive increase in size of the left supraorbital and infraorbital tumor motivated their surgical excision. The histological result was compatible with a neurofibroma. These uncommon orbital tumors are slow growing and affect the sensory nerves of the trigeminal nerve. Neurofibromas usually present progressive symptoms due to the orbital mass, proptosis, or visual changes although not in this case. Surgical removal is the only definitive treatment.